PENGARUH PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN SAKO UTARA TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DI NAGARI SAKO UTARA PASIA TALANG KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Irfandi, muhammad; Chandra, Deded (JURNAL BUANA, 2024)
The purpose of this study is to ascertain how community involvement affects the management of the Nagari Sako Utara forest. It is fascinating to explore in depth since this nagari eventually developed into a training facility for community-based forest management in West Sumatra.. This study used a quantitative descriptive method using the Likert scale method. The results of the research on community participation in village forest planning, with an average score of 2.75, were included in the very high category. As for community participation in forest implementation, the average score was 2. 53 fall into the very high category. Meanwhile, the income level of the North Sako forest farmer group comes from gallo-galo honey, the largest contributor to the income of the North Sako forest farmer group, with 3x harvests a year with a nominal value of around 4.5-8.5 million per yea